Cannibalism, predation, and refuges of juvenile blue crabs from a 37-year experiment - Anson H. Hines; Margaret A. Kramer; Kimberly D. Richie; L. David Smith; Robert Aguilar; Matthew B. Ogburn; Eric G. Johnson; Gregory M. Ruiz (Proceedings of the National Academy of Sciences, 2026)
This 37-y record (1989–2025) of field experiments tested seasonal and annual variation in predation on juvenile blue crabs ( Callinectes sapidus ) in a representative mesohaline site of Chesapeake Bay, USA, where the species is a dominant epibenthic predator and major fishery. We used replicated sets of individually tethered crabs to provide a relative index of lethal and sublethal predation rates on intermolt individuals as a function of size and habitats. Cannibalism by large adult crabs accounted for >97% of predation of juvenile crabs; predation by fish was not observed; and mortality from physiological stress was rare (<1%). Sampling by depth showed that juveniles occurred in nearshore shallows, while adults were in deeper water. Cannibalism was also depth-dependent: Rates were high at 75 cm depth; intermediate at 40 cm; and lowest at 15 cm shallows, which provided partial refuge. Cannibalism was size-dependent: 30 to 50 mm juveniles experienced high rates of predation; 90 to 110 mm preadults had low rates; and >120 mm adults had no predation. Cannibalism rates on juveniles varied seasonally, peaking during summer when adult crabs were most active; no tethering predation occurred in cold months. Variation in adult crab abundance accounted for 51% of annual variation in predation on tethered juveniles. Cannibalism by adult blue crabs provides a density-dependent regulation of juveniles by adults, with juvenile survivorship dependent on shallow-water refuge habitats in the mesohaline zone of the estuary. The refuge habitat appears increasingly restricted both by predatory fish common in high and recently introduced in low salinities, and by shoreline hardening.